Etiology of oak decline in Spain - Gallego, F. J.; de Algaba, A. Perez; Fernandez-Escobar, R. (European Journal of Forest Pathology, 1999)
In different areas of Extremadura, Western Spain, soil samples were taken at the bottom of holm oak (Quercus ilex) trees that were showing decline symptoms. Half of each sample was sterilized, and acorns were sown in both sterilized and nonsterilized soil samples. The resulting seedlings were used as baits for the isolation of fungi. Seedlings growing on the natural, nonsterilized substrate were characterized by having a lower vegetative growth than the ones growing on the sterilized soil samples, and most of them died. Phytophthora dnnamomi was consistently isolated from their roots. Fusarium oxysporum was also isolated as well as different species of Pythium, although to a lesser extent. Pathogenicity tests were performed on holm oak seedlings with five different isolates of P. chinnamomi, with F. oxysporum, Pythium and with a mixture of the three fungi. All the inoculated seedlings with P. chinnamomi developed root rot and grew slowly, and 35.7% of them died up to the end of the experiments. P. chinnamomi was consistently isolated from their roots, indicating that this fungus is the causal agent of holm oak decline. However, F. oxysporum caused similar symptoms on oak seedlings as P. chinnamomi, and was isolated also from the roots, although its frequency was lower than that of. P. cinnamomi.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Holm oak; Oak decline; Pathogenicity; Phytophthora cinnamomi (PG)

Etiology of oak decline in Spain - Gallego, F J; de Algaba, A Perez; Fernandez-Escobar, R (European Journal of Forest Pathology, 1999)
In different areas of Extremadura, Western Spain, soil samples were taken at the bottom of holm oak (Quercus ilex) trees that were showing decline symptoms. Half of each sample was sterilized, and acorns were sown in both sterilized and nonsterilized soil samples. The resulting seedlings were used as baits for the isolation of fungi. Seedlings growing on the natural, nonsterilized substrate were characterized by having a lower vegetative growth than the ones growing on the sterilized soil samples, and most of them died. Phytophthora dnnamomi was consistently isolated from their roots. Fusarium oxysporum was also isolated as well as different species of Pythium, although to a lesser extent. Pathogenicity tests were performed on holm oak seedlings with five different isolates of P. chinnamomi, with F. oxysporum, Pythium and with a mixture of the three fungi. All the inoculated seedlings with P. chinnamomi developed root rot and grew slowly, and 35.7% of them died up to the end of the experiments. P. chinnamomi was consistently isolated from their roots, indicating that this fungus is the causal agent of holm oak decline. However, F. oxysporum caused similar symptoms on oak seedlings as P. chinnamomi, and was isolated also from the roots, although its frequency was lower than that of. P. cinnamomi.
Keywords: Holm oak; Oak decline; Pathogenicity; Phytophthora cinnamomi (PG)